PENGARUH KOMPETENSI APARATUR, PEMANFAATAN SISTEM INFORMASI KEUANGAN DAN PERAN INTERNAL AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA PALU - Ngguna, Ruswanto (Katalogis, 2017)
This research aims to describe the influence of apparatus competence, utilization of financial information systems and the role of internal audit on the quality of local government financial statements of Palu City. This research type was quantitative with survey research method. The sample in this research was the leader and staff of the regional finance management unit as much as 70 respondents, the sample was taken using purposive sampling technique. The research data were collected by using questionnaires and interviews. Validity Test of questionnaire using product moment and reliability test using split half. Hypothesis test was used multiple regression analysis. The research Â results show that; First, apparatus competence have a significant effect on the quality of the financial statements of Palu city government. Second, the utilization of financial information system have insignificant effect on the quality of financial statements of Palu city government. And the last, the internal audit role has a significant effect on the quality of the financial statements of Palu city government.